Conjugated linoleic acid improves glucose utilization in the soleus muscle of rats fed linoleic acid–enriched and linoleic acid–deprived diets - Fariña, Ana Clara (2014)
The effect that conjugated linoleic acid (CLA) has on glucose metabolism in experimental animals depends on nutritional conditions. Therefore, we hypothesized that CLA improves glucose utilization and insulin sensitivity in rats fed different levels of dietary linoleic acid (LA). We investigated the effect of CLA on the uptake, incorporation, and oxidation of glucose and glycogen synthesis in the soleus muscle of rats who were fed either LA-enriched (+LA) or LA-deprived (−LA) diets, under basal conditions and in the absence or presence of insulin and/or palmitate. For 60 days, male Wistar rats were fed 1 of 4 diets consisting of +LA, −LA, or +LA and −LA supplemented with CLA. Nutritional parameters and soleus glucose metabolism were evaluated. Under basal conditions, CLA enhanced soleus glucose oxidation, whereas increased glucose uptake and incorporation were observed in the −LA + CLA group. Conjugated linoleic acid–supplemented rats presented a lower response to insulin on glucose metabolism compared with non–CLA-supplemented rats. Palmitate partially inhibited the effect of insulin on the uptake and incorporation of glucose in the +LA and –LA groups but not in the +LA + CLA or −LA + CLA groups. Dietary CLA increased glucose utilization under basal conditions and prevented the palmitate-induced inhibition of glucose uptake and incorporation that is stimulated by insulin. The beneficial effects of CLA were better in LA-deprived rats. Conjugated linoleic acid may also have negative effects, such as lowering the insulin response capacity. These results demonstrate the complexities of the interactions between CLA, palmitate, and/or insulin to differentially modify muscle glucose utilization and show that the magnitude of the response is related to the dietary LA levels.